Integration of sustainability into corporate strategy: A case study of the textile and clothing industry - Peters, J. (2020)
More and more Textile and Clothing (T&C) companies decide to integrate sustainability into their corporate strategy. Although the T&C industry linked to sustainability has been the subject of various studies, to the best of our knowledge, little research exists, which focuses on the integration of sustainability into corporate strategy in special regards to European T&C companies with global value chains. This paper explores a set of institutional, organizational and individual drivers and barriers for the integration of sustainability into corporate strategy of a European T&C company. The results are based on a case study of the exemplary VAUDE – a family-owned, sustainable outdoor outfitter company and stand in accordance with Institutional Theory and Stakeholder Theory as theoretical frameworks explaining why companies deal with sustainability. The determined drivers are dependent on a coherence of all levels of analysis, i.e. institutional, organizational and individual. The barriers are of institutional and organizational nature only. The findings present significant suggestions for other T&C companies that seek to integrate sustainability into their corporate strategy and for the T&C industry to create a sustainability friendly environment to drive more T&C companies to become sustainable. It further supports T&C companies in identifying potential barriers, how to overcome them and successfully integrate sustainability into their corporate strategy. The results reveal that it only works if sustainability is strongly integrated into one’s corporate strategy and deeply anchored in all departments and daily tasks of a T&C company.